ADOPTION OF AI IN RECRUITMENT: IMPLICATIONS FOR BIAS, EFFICIENCY, AND CANDIDATE EXPERIENCE - Bungaran Panggabean; Welis Raldianingrat; Baharudin Baharudin; Irham Natsir K (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
However, while the integration of AI into recruitment practices offers numerous potential benefits, it also raises critical concerns regarding fairness, transparency, and candidate experience. A central issue is the risk of algorithmic bias. The purpose of this study is to analyze the adoption of Artificial Intelligence (AI) in the recruitment process: its implications for bias, efficiency, and candidate experience. This study employs a literature review methodology to systematically analyze and synthesize existing research on the adoption of Artificial Intelligence (AI) in recruitment, with a particular focus on three interrelated aspects: bias, efficiency, and candidate experience. This literature review explored the multifaceted implications of Artificial Intelligence (AI) adoption in recruitment, focusing on three key dimensions: bias, efficiency, and candidate experience. The findings reveal that while AI technologies offer substantial benefits in terms of operational speed and cost reduction, they also introduce significant ethical, social, and psychological challenges.